From the perfect competition to the Coasian Nature of the Firm. - Carvalho, Sónia de (2016)
The Coasian Nature of the Firm merges neoclassical and institutional economics approaches, by applying the marginal analysis to decision-making processes of the company, with consequences on their structure and size. This paper aims at drawing the evolution of economic theory from perfect competition model to the Coasian Nature of the Firm, in order to explain the main influences that shaped one of the Transaction Cost Economics underpinnings.